Pengembangan Lms “SIPANDA” Untuk Mendukung Pembelajaran Problem Based Learning Pada Elemen Basis Data Kelas XI RPL SMK Negeri Tambakboyo - Rahmatul Ummah; Riza Akhsani Setyo Prayoga (CV. SINAR HOWUHOWU, 2026)
Database learning at SMK Negeri Tambakboyo still relies on multiple platforms, resulting in learning activities that are not integrated into a single system. This condition causes the delivery of learning materials, assignment submission, and learning management to be less organized. This study aims to develop a Moodle-based LMS called “SIPANDA” to support Problem Based Learning (PBL) in the Database subject for Grade XI Software Engineering students and to determine users’ acceptance of the developed system. This research employed the R&D method using the ADDIE development model. The research subjects consisted of 34 students and one Database teacher at SMK Negeri Tambakboyo. Data were gathered through observations, interviews, expert validations, Blackbox Testing, and the Technology Acceptance Model (TAM) questionnaire. The collected data were analyzed using descriptive quantitative techniques. The results showed that “SIPANDA” was successfully developed in accordance with learning needs. The validation results obtained scores of 93% from media experts, 91% from subject matter experts, and 91% from instructional module experts, all categorized as highly feasible. Blackbox Testing indicated that all system features functioned properly according to their intended design. Furthermore, the TAM evaluation demonstrated a very high level of user acceptance across all measured constructs. Therefore, “SIPANDA” is considered highly feasible and well accepted as a learning medium to support the implementation of Problem Based Learning in the Database subject.